Дослідження методів кластеризації даних для реалізації рекомендаційної функції CRM-системи мережі кінотеатрів - Одинцова, В. О. (ХНУРЕ, 2024)
This work is showing the investigation of the clustering methods for the web cinema CRM-system «Cinema Art» that helps to implement the recommendation function for the films. The article covers the research of three clustering methods: k-means, hierarchical clustering and DBSCAN clustering. Based on the research one of the clustering methods is developed on Python using an open-source platform Anaconda. The data for the clustering research was used from an open dataset MovieLens.
Keywords: CRM-система; мережа кінотеатрів; кластеризація даних